(RE)PRODUCING A PEACEFUL CANADIAN CITIZENRY: A LESSON ON THE FREE TRADE OF THE AMERICAS QUEBEC CITY SUMMIT PROTESTS - Mahrouse, Gada (Canadian Journal of Education/Revue canadienne de l'éducation, 2006)
In this article, I argue that despite common assumptions that peace education efforts achieve social change, it is often a normalizing, nation‐building project that obscures hierarchies of power. Focussing on a lesson from a popular peace education program currently used in Canadian schools, I have analyzed the convergences between peace and citizenship education and consider the implications of pedagogies that encourage peace as a personal choice and responsibility. I call for an approach to peace education that promotes critical thinking on how knowledge is produced. Key words: peace education, citizenship, nation‐building, knowledge production, non‐violent protest On suppose communément que la promotion de l’éducation pour la paix fait évoluer la société, mais l’auteure soutient dans cet article qu’elle est plutôt un projet national normatif qui camoufle des pouvoirs hiérarchiques. À l’aide d’une leçon faisant partie d’un programme d’éducation pour la paix très utilisé dans les écoles canadiennes, l’auteure analyse les convergences entre la paix et l’éducation à la citoyenneté et s’intéresse aux implications des pédagogies qui encouragent la paix comme un choix et une responsabilité personnels. Elle prône une approche qui favorise la pensée critique au regard du mode de production du savoir. Mots clés : éducation pour la paix, citoyenneté, développement d’un pays, production du savoir, protestation non violente.